Solid-state valence tautomeric octahedral CoII[(BQ-N-Cat)]20 complex formation via ligand-centered phenolic C–O bond breaking and Co–O bond making. Issue 80 (19th September 2016) - Mondal, Manas Kumar; Tiwari, Archana; Mukherjee, Chandan
Abstract : An octahedral Co II [(BQ-N-Cat)]2 0 complex was formed by ligand-centered phenolic C–O bond cleavage. The complex showed solid-state valence tautomerism that is triggered by lattice solvent molecule. Abstract : Ligand H4 L O(AP/AP) underwent ligand-centered C–O bond cleavage during a complexation reaction with Co(ii )-salt. The thus formed octahedral Co II [(BQ-N-Cat)]2 0 complex showed valence tautomerization in the solid state. While the process was triggered by the presence of lattice solvent, the nature of the solvent molecule has less effect on the process.